Diagnostic accuracy of patch test in children with food allergy. Issue 5 (11th May 2015) - Caglayan Sozmen, Sule; Povesi Dascola, Carlotta; Gioia, Edoardo; Mastrorilli, Carla; Rizzuti, Laura; Caffarelli, Carlo
Abstract Background The gold standard test for confirming whether a child has clinical hypersensitivity reactions to foods is the oral food challenge. Therefore, there is increasing interest in simpler diagnostic markers of food allergy, especially in children, to avoid oral food challenge. The goal of this study was to assess the diagnostic accuracy of atopy patch test in comparison with oral food challenge. Methods We investigated 243 children (mean age, 51 months) referred for evaluation of suspected egg or cow's milk allergy. Skin prick test and atopy patch test were carried out, and after a 2 weeks elimination diet, oral food challenge was performed. Results Two hundred and forty‐three children underwent OFC to the suspected food. We found clinically relevant food allergies in 40 (65%) children to egg and in 22 (35%) to cow's milk. The sensitivity of skin prick test for both milk and egg was 92%, specificity 91%, positive predictive value 35%, and negative predictive value of 93%. Sensitivity, specificity, positive predictive value, and negative predictive value of atopy patch test for both milk and egg were 21%, 73%, 20%, and 74%, respectively. Conclusion Our study suggests that there is insufficient evidence for the routine use of atopy patch test for the evaluation of egg and cow's milk allergy. OFC remains gold standard for the diagnosis of egg and milk allergy even in the presence of high costs in terms of both time and risks during application.